Truth's a Dog Must to Kennel by Tim Crouch - Yeliz Biber Vangölü (Theatre Academy)
This is a review of Truth’s a Dog Must to Kennel (2022) by the contemporary British theatre practitioner Tim Crouch. Premiered at the Royal Lyceum Theatre as a part of the Edinburgh Fringe Festival in 2022, the play is a direct outcome of Crouch’s experience, both as a human being and a theatre maker, of the COVID-19 pandemic and his thoughts on the death of theatre as an art form during the pandemic. This review is based on the stage production of the play at York St John Creative Art Centre as a part of York International Shakespeare Festival in 2023.